Behavioral science students as training facilitators of outbound seafarers in the prevention of HIV/AIDS - Imperial, Reynaldo H.
The intention of this study is to determine whether Behavioral Science students of a college in a state institution in Manila can be trained to conduct the Pre-departure Orientation Program (PDOS) for outbound Filipino seafarers as an alternative to the supplier and NGO-based PDOS implementors. Methods: The students were trained to conduct a seminar using approved curriculum by the Philippine Overseas Administration Office. These students prepared an instructional design based on the module that the Philippines National Aids Council (PNAC) has recommended to be used in the PDOS training. A rubric for both the quality of the instructional design and the effectiveness of the student volunteers in adult learning were used to rate the proficiency of the students. A pre- and post-test training design was used to determine if seafarers are able to remember key HIV/AIDS prevention messages that were discussed. Also, an intended behavioral change discussion was utilized to determine the extent by which these seafarers will adopt safer sexual practices including sexual abstinence while on various ports of the disembarkation. Results: The study showed that when instruction is focused and the information given is useful to adult learners the seafarers, it is possible to pass correct information on the prevention and mitigation of the ill effects of HIV was effective because of the very good quality of the instructional design that the student volunteers were able to produce. Intended behavior change was shared by the seafarer in the small group discussions that were held. Discussions: Behavioral Science students can be trained to be effective facilitators of learning through training designed that was intended to inform seafarer of the perils of HIV and AIDS infection using an instructional design that sought to provide learners with relevant and useful information about the infection. This also translated in the ability of learners to remember key prevention and treatment options as well as decide to change their risky sexual practices.